Sulejman Bajraktarević and His Work in the Area of Oriental Studies - Gazić, Lejla (Prilozi za orijentalnu filologiju, 2017)
Sulejman Bajraktarević was born on September 3, 1896 at Gornji Vakuf. He was educated in his native town, then in Istanbul and Sarajevo, and in Vienna he studied international trade, where he graduated in 1922. Till 1948 he worked in his profession, but throughout that period his·interest for oriental studies developed, and the followed closely the development of oriental studies in our country and the world. In 1948, at the age of 52, Sulejman Bajraktarević left the job of an economist, to devote all his time to oriental studies. He began to work at the Oriental collection of the Yugoslav Academy of Science and Art; in Zagreb, where he was to remain it’s only specialist till July 31, 1969. Because of the nature of the work, Sulejman Bajraktarević directed his research in three directions: - research primarily concerning the work on the manuscripts and archives in Croatia, - archive work in connection with the collection and - all kinds of administrative work. Sulejman Bajraktarević died on March 20, 1977 in Zagreb. The list of works of S. Bajraktarević from the area of oriental studies consists of 17 papers in the publications, one translation and six reviews, which have been given here in chronological order.